RESEARCH ON MULTI FLEXIBLE BODY DYNAMIC CHARACTERISTICS OF LIFTING MECHANISM OF NEUTRON STRESS SPECTROMETER - LI YongBo; WU YunXin; GONG Hai; LI Yang (Jixie qiangdu)
First,the lifting mechanism of neutron spectrometer sample table was designed. Then,the part flexible models and flexible multibody model were built by using ANSYS and ADAMS. Finally,the part flexible models and flexible multibody model were analyzed when lifting mechanism lifts at the highest point and sliding table center moves along the X or Y axis. The results indicate that Z direction’s average deformation is maximum among all direction deformations of sliding table center,which is 30. 12μm. Outer cylinder take up the largest proportion of the deformation in X direction,which is 75. 8%,middle cylinder take up the largest proportion of the deformation in Y direction,which is 91. 32%,inner cylinder take up the largest proportion of the deformation in Z direction,which is 89. 36%. Of eight guide rails of lifting mechanism,four guide rails between inner and middle cylinder are under uniform load,other four guide rails between middle and outer cylinder are under non-uniform load. The findings of the research could guide the design of the neutron spectrometer sample table. In order to develop a high precision neutron stress spectrometer sample platform,the stability and reliability of the sample table is achieved.